GWAS Mediated Elucidation of Heterosis for Metric Traits in Cotton (Gossypium hirsutum L.) Across Multiple Environments - Sarfraz, Zareen; Iqbal, Muhammad Shahid; Geng, Xiaoli; Iqbal, Muhammad Sajid; Nazir, Mian Faisal; Ahmed, Haris; He, Shoupu; Jia, Yinhua; Pan, Zhaoe; Sun, Gaofei; Ahmad, Saghir; Wang, Qinglian; et al. (Frontiers in Plant Science, 2021)
Plant breeding has widely exploited the heterosis (often considered as hybrid vigor) phenomenon to increase agricultural productivity for about a century. F1 hybrids can manifest substantial outperformance in yield and vegetative growth compared with the progenitors attributed to heterozygous combinations mitigate for deleterious mutations occurring in each genome. However, only fragmented knowledge is available related to underlying genes and processes leading to heterosis. Though cotton is amongst highly privileged crops, its improvement programs involving heterosis exploitation are still parched for significant accomplishments to make it adaptable in different agro-ecological zones. Here, F1 hybrids derived from mating of a diverse Upland Cotton germplasm with commercially valuable cultivars in Line × Tester fashion, were evaluated across multiple environments for their ten metric traits. Their ten metric traits were dissected into five different heterosis types and Specific Combining Ability (SCA). Subsequent genome-wide predictions along-with association analyses uncovered a set of 281 highly significant key SNPs and 254 heterotic Quantitative Trait Nucleotides (hQTNs) related to agronomic and fiber quality traits. Integration of genome wide association study with RNA-sequence analysis yielded 290 candidate genes in vicinity of key SNPs. Fiber micronaire (MIC) came up with a maximum number of associated genes, i.e., 45. All the candidate genes got identified in association with HETEROSIS of quoted traits. These genes may be considered as a resource for plant breeders in order to achieve pace lying in the way of stagnant improvement programs primarily focused on yield as well as fiber quality of cotton.